Assessment of Quality of Antenatal Care Services and Its Determinant Factors in Public Health Facilities of Hossana Town, Hadiya Zone, Southern Ethiopia: A Longitudinal Study - Trhas Tadesse Berehe; Lebitsi Maud Modibia (Hindawi Limited, 2020)
Background. Antenatal care is a care that links the woman and her family with the formal health system, increases the chance of using a skilled attendant at birth, and contributes to good health through the life cycle. Inadequate care during this time breaks a critical link in the continuum of care and affects both women and babies. Therefore, the main aim of this study was to determine the quality of ANC in Hadiya Zone, Southern Ethiopia. Method. A longitudinal facility-based study design was conducted among 1123 mothers whose gestational age of less than 16 weeks was identified and followed until birth and 40 days after birth to detect whether they gained the acceptable standard of quality of ANC from July 2017 to June 2018. A structured, predefined, and pretested observation check list and Likert scales were employed to obtain the necessary information after getting both written and verbal consent from the concerned bodies and study participants. Data was entered into Epi Info version 3.5 and transferred to STATA Version 14 software and cleaned by reviewing frequency tables, logical errors, and checking outliers. Generalized estimating equation (GEE) analysis was applied to get the average response observation of each visit of quality of ANC in the health facilities. Result. This study showed that the overall magnitude of good quality of antenatal care service that was provided in the whole visit at Hosanna Town's public health facilities was 1230 (31.38%). The most frequently identified problems were inability to take full history, lack of proper counseling, poor healthcare provider and client interaction, and improper registration and there was a variation in providing quality of care in each visit. Quality of antenatal care was significantly associated with residence, educational status gravidity, parity, and visit. In conclusion, the overall quality of antenatal care is low, so the health facilities need further modification on the identified problems.